2017
DOI: 10.21037/jtd.2017.02.40
|View full text |Cite
|
Sign up to set email alerts
|

Uniportal video-assisted thoracic surgery colorectal lung metastasectomy in non-intubated anesthesia

Abstract: Background: More than ten years ago we started a program of video-assisted thoracic surgery (VATS) lung metastasectomy in non-intubated local anesthesia. In this study we investigated the effectiveness and long term results of this combined surgical-anesthesiological technique. Methods: Between 2005 and 2014, 48 patients (25 men and 23 women) with pulmonary oligometastases from colorectal cancer, at the first episode, underwent VATS metastasectomy under non-intubated local anesthesia. Three patients required i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 20 publications
(16 reference statements)
0
36
0
Order By: Relevance
“…Our recent studies showed that the same effects of lower immunological suppression and reduced inflammatory response can be detected when comparing uniVATS and multiport VATS (68). As a consequence, given the lower trauma of uniVATS, it is hypothesizable that this technique could favor an improved long-term survival and impact on tumor recurrence in patients with primary or secondary lung cancers (69).…”
Section: The Recent Progressmentioning
confidence: 89%
See 2 more Smart Citations
“…Our recent studies showed that the same effects of lower immunological suppression and reduced inflammatory response can be detected when comparing uniVATS and multiport VATS (68). As a consequence, given the lower trauma of uniVATS, it is hypothesizable that this technique could favor an improved long-term survival and impact on tumor recurrence in patients with primary or secondary lung cancers (69).…”
Section: The Recent Progressmentioning
confidence: 89%
“…It is, to our knowledge, the first dedicated to nonintubated thoracic surgery in the literature. During more than a decade this program achieved a consistent amount of knowledge about the surgery in awake patients and produced a great number of scientific publications (68,69,81,84,(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105). In our program we initially privileged anesthesia delivered through an epidural catheter with a fully awake and collaborative patient (96)(97)(98)(99).…”
Section: The Awake Anesthesia In Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of the surgical accesses now possible through the development of high definition camera, energy devices, multi-articulated endoscopic stapler, represents an indubitable advantage in patients under non-intubated anesthesia. We have recently published the results of this mixed surgical/anesthesiologic approach demonstrating better early and similar long-term outcomes when compared with traditional intubated multiport-VATS metastasectomy (33).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery of lung metastases has been performed since the beginning of our experience [ 9 ]. Early operations were done under epidural anesthesia and three-port video-assisted thoracic surgery (VATS) [ 10 ] but starting from 2005, lung metastasectomies have been preferably accomplished through a unique thoracoscopic access under non-intubated anesthesia [ 11 ].…”
Section: Introductionmentioning
confidence: 99%